Estudio de factibilidad para la creación de una empresa catering industrial para empresas PYMES en el municipio de Funza (2019)
The following degree project is about a feasibility study for the creation of an industrial catering refreshments company for companies located in the municipality of Funza, exactly in the Celta Trade Park industrial park, which currently has 81 SME companies.To determine if the creation of the company is feasible, profitable and viable, seven stages were carried out in the project, where for the development of each of them, different qualitative and quantitative investigations were carried out, with primary and secondary sources. Determining as first the unsatisfied demand of the companies that are in the park, through virtual and face-to-face surveys, the development of the products and services that are offered in order to meet this need, through different variables such as nutrition, quality, punctuality and price. Integrating production processes with administrative processes and sales processes. Internal and external factors are analyzed in the project, applying the current legal and environmental norms currently governed by the Colombian Constitution, and finally the project is based on calculations projected with the CPI variable, analyzing the financial indicators more representative for investors, determining if the project is feasible, profitable and viable.